The party line [large type] - Brown, Carolyn, 1948- (Center Point Large Print, 2025)
"Returning home to Ditto, Texas, is bittersweet for Lila Matthews. Her dear and feisty Aunt Gracie has passed away, leaving Lila her estate. That includes a centuries-old house, a field of the freshest strawberries in Atascosa County, more money than Lila can count, and a secret Aunt Gracie took to her grave. All the angels in heaven won't be able to pry it out of her. For more than eighty years, generations of folks in Ditto have whispered and gossiped about what the secret could be. When Lila inherits Aunt Gracie's legacy, ears perk up and tongues start wagging. As Lila reacquaints herself with locals, finds warmth in family--extended and otherwise--and cozies up to a handsome new neighbor, she begins collecting clues to the past. They're revealing an Aunt Gracie nobody knew--and a life of rebellion, broken hearts, and selfless love that affected more people than anyone realized. Whatever reason Aunt Gracie had for leaving Lila the secret, will it now be Lila's secret to keep?"--